Status of the population structure of the mangrove crab Ucides cordatus (Decapoda: Ocypodidae) on the Piraquê-açu River estuary, Espírito Santo, Brazil - Rita de Cássia Conti; Rosebel Cunha Nalesso (Brazilian Journal of Oceanography, 2010)
The land crab Ucides cordatus is a keystone species of neotropical mangrove forests and an important resource of the artisanal fisheries. The spatial and temporal distribution of U. cordatus in the mangrove area of the Piraquê-açu river estuary was determined following a longitudinal estuarine salinity gradient (lower, middle, upper estuary) and along the vertical intertidal gradient. The numbers of open and closed burrows were counted monthly on fixed transects, the inhabiting crabs were caught, sexed and the carapace width measured, during 1 year. The mean crab density was 2.5 ind.m-². The highest crab density (3.9 ind.m-²), linked to high numbers of juvenile crabs, was found on the upper estuary and correlated with lower salinities. High intertidal levels had higher crab densities than lower intertidal levels, except in the upper estuary. Males were smaller than females; the mean carapace width of the population was 4.89 cm, below the minimum legal harvesting size (6 cm). The predominance of females over males at some sites (especially close to villages) brought out the advanced level of overfishing of this U. cordatus population and highlights the urgent need of management actions. O caranguejo Ucides cordatus é uma espécie chave nos manguezais da região neotropical e um importante recurso pesqueiro para populações tradicionais. A distribuição espacial e temporal de U. cordatus no manguezal do Rio Piraquê-açu foi estudada ao longo de um gradiente de salinidade, no estuário inferior, médio e superior na faixa entre-marés. Mensalmente durante um ano. O número de tocas abertas e fechadas ao longo de transectos fixos, foi contado mensalmente, ao longo de um ano, e os caranguejos capturados foram sexados e medidos quanto à largura da carapaça, sendo posteriormente liberados. A densidade média de caranguejos foi de 2,5 ind.m-². A maior densidade (3,9 ind.m-²), juntamente com o maior número de jovens, foi encontrada na parte superior do estuário, correlacionada com baixas salinidades. Nos níveis mais altos de maré a densidade de caranguejos sempre foi alta, exceto na região superior do estuário. Os machos foram menores do que as fêmeas; o tamanho médio da carapaça da população total foi de 4,89 cm, abaixo do tamanho legal permitido para captura (6 cm). A predominância de fêmeas sobre machos em alguns pontos, principalmente próximos às vilas, revela o avançado nível de sobreexplotação da população de U. cordatus, evidenciando a necessidade urgente de ações fiscalizadoras.